2020
DOI: 10.1038/s41467-020-16722-7
|View full text |Cite
|
Sign up to set email alerts
|

m5C modification of mRNA serves a DNA damage code to promote homologous recombination

Abstract: Recruitment of DNA repair proteins to DNA damage sites is a critical step for DNA repair. Post-translational modifications of proteins at DNA damage sites serve as DNA damage codes to recruit specific DNA repair factors. Here, we show that mRNA is locally modified by m5C at sites of DNA damage. The RNA methyltransferase TRDMT1 is recruited to DNA damage sites to promote m5C induction. Loss of TRDMT1 compromises homologous recombination (HR) and increases cellular sensitivity to DNA double-strand breaks (DSBs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 46 publications
4
121
0
1
Order By: Relevance
“…Modification of mRNA by m C is important for diverse biological processes including the progression of bladder cancer, HIV-1 infection, and developmental progressions in zebrafish, Arabidopsis thaliana, and rice (13,(17)(18)(19), suggesting that cytosine methylation is a powerful regulator of cellular processes at the epitranscriptomic level (16). In other studies, pathways involving m 5 C-modified transcripts have been found to include DNA repair and homologous recombination (20). Specific methyltransferases (m 5 C writers) in various species include NSUN2 in humans, TRM48 in Arabidopsis thaliana, and OsNSUN2 in rice.…”
Section: Introductionmentioning
confidence: 94%
“…Modification of mRNA by m C is important for diverse biological processes including the progression of bladder cancer, HIV-1 infection, and developmental progressions in zebrafish, Arabidopsis thaliana, and rice (13,(17)(18)(19), suggesting that cytosine methylation is a powerful regulator of cellular processes at the epitranscriptomic level (16). In other studies, pathways involving m 5 C-modified transcripts have been found to include DNA repair and homologous recombination (20). Specific methyltransferases (m 5 C writers) in various species include NSUN2 in humans, TRM48 in Arabidopsis thaliana, and OsNSUN2 in rice.…”
Section: Introductionmentioning
confidence: 94%
“…A recent report showed that DNMT2 (Figure 3B) is recruited to DNA damage sites, where it deposits m 5 C onto the DNA damage-associated mRNAs and contributes to R-loop formation. The m 5 C and DNMT2-mediated R-loops facilitate the homologous recombination (HR) and DNA repair of DSBs [247].…”
Section: A and Rmps Associated R-loop Formation On Dna Damage-assocmentioning
confidence: 99%
“…Repair with high fidelity is essential for genetic stability and good health [67]. In some cases, mRNA serves as a DNA damage code and promotes homologous recombination [68]. As a result, the entrance of any foreign mRNA inside human cells poses a risk to the stability of the cellular genome of the recipient.…”
Section: Sars-cov-2 Vaccine Developmentmentioning
confidence: 99%